Exclusive Breastfeeding Based On The Characteristics Of Breastfeeding Mothers In Kutelintang Village, Belangkejeren District, Gayo Lues Regency - Khairunnisa Batubara; Resmi Pangaribuan (LLDIKTI Wilayah 1, 2021)
Exclusive breastfeeding is one way to obtain good growth and development of infants. Because milk contains all the essential nutrients that babies need for growth and development and contains antibodies to the baby's immune. The purpose of this study was to determine the relationship of the characteristics of nursing mothers to exclusive breastfeeding in the village Kutelintang Belangkejeren District of Gayo Lues District. This research is an analytical method with a sample size of 19 people. The instrument in this research is a questionnaire that contains the characteristics of nursing mothers and 7 the question of exclusive breastfeeding. The results showed that as much as 44.6% with sig. 0.027 this can be seen from the characteristics of the mother's relationship with breastfeeding simultaneously. And after statistical analysis test using Pearson chi square it was found that there was no significant relationship between the age of breastfeeding mothers and exclusive breastfeeding (p = 0.291). However, there was a significant relationship between the education level of breastfeeding mothers and exclusive breastfeeding and exclusive breastfeeding (p = 0.007). From the results of this study are expected to be useful for nursing mothers, researchers and for society kutelintang village in order to improve and provide counseling tentangg benefits of exclusive breastfeeding.